Euthanasia in Clinical Toxicology Perspective: Legal Aspects, Morality, and Health Risks - Denny Vianto; Yusian Eri Fitria; Anis Mashdurohatun; Sri Endah Wahyuningsih; Jawade Hafidz; Deni Setiyawan; Ana Fauzia (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article examines the implications of clinical toxicology in the practice of euthanasia, focusing on aspects of law, morality and health risks. Euthanasia involving the use of toxic substances raises various dilemmas, including the patient’s right to choose a proper death and the doctor’s responsibility to protect life. Through a normative juridical method, this study examines the regulation of the use of toxic substances in euthanasia procedures in countries that legalize this practice. The results show the need for standardization of procedures, legal protection for medical practitioners, as well as stricter ethical guidelines to avoid abuse.